The Effect Of Using The THELEN Model (Group Investigation) In Solving Mathematical Problems Among Female Students Of The First Intermediate Grade In Mathematics (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to identify the effect of using the THELEN (group investigation) model in solving mathematical problems of first-grade intermediate students and their achievement in the mathematics subject, in order to verify the goal of the research, the researcher formulated the following null hypothesis (There is no statistically significant difference at the level of significance (0.05) between the average scores of the students of the experimental group who studied on according to the THELEN model (group investigation) and the average scores of the control group that studied on the usual method for the mathematical problem solving test), The research sample included (51) students who were chosen intentionally, as the sample was divided into two groups, one of them is an experimental group consisting of (25) female students who studied according to Thelen (group investigation) model and the other control group was made up of (26) female students who studied according to the usual method, to achieve the goal of the research, the researcher prepared a mathematical problem-solving test consisting of (30) paragraphs of a kind of multiple choice؛ The validity, reliability and distinction of the test paragraphs were verified, and the researcher used the appropriate statistical means to complete her research, and the results showed that the students of the experimental group who studied according to the model of Thelen (group investigation) outperformed the students of the control group who studied according to the usual method and in light of the result reached by the current research, the researcher developed a set of conclusions, recommendations and proposals.